Design for extreme scalability: a wordless, globally scalable COVID-19 prevention animation for rapid public health communication - Adam, Maya; Bärnighausen, Till; McMahon-Rössle, Shannon A. (Journal of global health, 2020)
To meet time-sensitive health communication needs during a global public health crisis, public health agencies need to explore simple, globally accessible messaging strategies and delivery platforms that lie outside of their comfort zones.